Is delayed surgery related to worse outcomes in native left-sided endocarditis? - Thitipong Tepsuwan (2018)
© SAGE Publications. Background Timing of surgery in the management of infective endocarditis is controversial, and there is still no definite conclusion on how early the surgery should be performed. This study focuses on the outcomes of surgery during the active period of infective endocarditis in consideration of the duration after diagnosis. Methods One hundred and thirty-four patients with active native valve infective endocarditis who underwent surgery from January 2006 to December 2013 were reviewed retrospectively. They were divided in 2 groups based on timing of surgery: early group (first week after diagnosis, n = 37) and delayed group (2 to 6 weeks after diagnosis, n = 97). Results Compared to the delayed group, the early group had significantly more patients in New York Heart Association class IV (81% vs. 43.3%), more mechanically ventilated (54.1% vs. 18.6%), more on inotropic support (62.2% vs. 38.1%), and hence a worse EuroSCORE II (14.8% vs. 8.8%). Operative mortality was comparable (5.4% vs. 10.3%) and 7-year survival was similar (77.4% vs. 74.6%). On multivariable regression analysis, delayed surgery did not impact on short- and long-term outcomes. Preoperative cardiac arrest and infection with Haemophilus, Actinobacillus, Cardiobacterium, Eikenella, or Kingella were risk factors for higher operative mortality. Predictors of poor 7-year survival were diabetes mellitus and acute renal failure. Conclusions Delayed surgery is not associated with worse outcomes. Both early and delayed approaches are safe and provide acceptable results. Timing of surgery should be tailored to each patient's clinical status, not based on duration of endocarditis alone.